Characterization of Interface Between Accurately Controlled Cu‐Deficient Layer and Cu(In, Ga)Se2 Absorber for Cu(In, Ga)Se2 Solar Cells (Phys. Status Solidi RRL 8/2018). Issue 8 (8th August 2018) - Nishimura, Takahito; Sugiura, Hiroki; Nakada, Kazuyoshi; Yamada, Akira
Abstract : Takahito Nishimura et al. (article no.1800129 ) recently succeeded in controlling a Cu‐deficient Cu(In, Ga)Se2 layer (CDL) on a Cu(In, Ga)Se2 (CIGS) surface by introducing a Se irradiation after the completion of the second stage in a threestage process during CIGS growth. The CDL on the surface causes the formation of a valence band offset between the CDL and CIGS because the Cu vacancies decrease the valence band maximum of the CDL, leading to the suppression of recombination at the CdS/CIGS interface in CIGS solar cells. In this article, the compositional and structural properties of an accurately controlled CDL/CIGS interface are investigated in detail. The ( 1 1 ¯ 2 ) plane in the CDL continuously grows on the ( 1 1 ¯ 2 ) plane in CIGS, resulting in only a small amount of dangling bonds at the interface and effectiveness of the CDL for high‐efficient CIGS solar cells.